From Picky Eaters to Nourished Explorers: Unveiling the Power of Responsive Feeding in Enhancing Young Children’s Nutrition - Karina Megasari Winahyu; Zulia Putri Perdani; Kartini Kartini; Astuti Astuti (Universitas Faletehan, 2023)
Implementing responsive feeding is essential for modifying the nutritional status and overall well-being of young children. The aim of this narrative review is to provide a thorough synthesis of the current evidence on responsive feeding and its impact on the nutritional status of young children. Searches were conducted in PubMed and Medline with keywords